Engaging stakeholders into an electronic patient-reported outcome development study: On making an HIV-specific e-PRO patient-centered. Issue 1 (March 2017) - Engler, Kim; Lessard, David; Toupin, Isabelle; Lènàrt, Andràs; Lebouché, Bertrand
Abstract: Background: The use of patient-reported outcome (PRO) measures in care and research is proposed to foster patient-centered care but this outcome may depend on stakeholder engagement in their development and implementation. Hence, we subsequently engaged HIV patients and clinicians into a study aimed at creating a new electronic PRO (e-PRO) for monitoring barriers to antiretroviral therapy adherence in HIV care. As detailed examples of such engagement are lacking, we describe our rationale, methods and first results of these engagement initiatives. Methods: We established a 10-member patient committee. Periodic focus groups engaged HIV clinicians. Focus groups were conducted with both groups to assess needs for the e-PRO: 3 mainly with patient committee members ( n =12) and 5 with clinicians ( n =31). Content on the e-PRO׳s targeted concept (adherence barriers) was analysed with Grounded Theory (patients) and with typological analysis (clinicians). Results: Patients' discussions reflected three temporal categories (imprinting, domino effects, future-shadowing) and one overarching theme (weathering) in the experience of adherence and its many barriers. Latent within HIV clinicians' discussions was a typology of patients organized by distinct barriers to adherence, life conditions, and attitudes to care. Discussion: Results emphasize the lived experience of managing barriers and its complexity. They suggest the new e-PRO should accommodate patient diversity, contextualize scores longitudinally, and address the personal significance of individual barriers (e.g., distressfulness) beyond their mere presence. These initial results and the opportunities presented by our long-term engagement initiatives should ensure the production of a useful and used patient-centered e-PRO. Highlights: New e-PROs for clinical practice must be useful to both patients and clinicians. Thus, we engaged stakeholders into our HIV-specific e-PRO development study. We added a patient committee, stakeholder liaison agent and focus groups with clinicians. This research program is now devoted to developing a patient-centered e-PRO. This paper details methods of stakeholder engagement in e-PRO development and preliminary results.